Hot deformation behaviors of arc melted and heat treated NbSi based ultrahigh temperature alloys. (November 2019) - Tang, Ye; Guo, Xiping
Abstract: The difference in hot deformation behaviors of arc melted (AM) and heat treated (HT) NbSi based ultrahigh temperature alloys has been investigated at temperatures of 1250 and 1410 °C respectively and a strain rate of 0.001 s −1 . AM alloy exhibits a higher peak stress than HT alloy. The evolution of deformed microstructure signified by the change in silicide shape and size, has been obviously restrained in HT alloy compared to the AM one. During deformation at 1250 °C, continuous dynamic recrystallization (CDRX) of Nbss has been promoted in AM alloy compared with HT alloy, while CDRX process of Nb5 Si3 shows little difference in both alloys. At a higher deformation temperature of 1410 °C, CDRX process of both Nbss and Nb5 Si3 is slower in AM alloy than in HT alloy. Smaller Nbss grains have formed in AM alloy than in HT alloy after a height reduction of 60%, leading to a larger stress reduction during flow softening in the former. Graphical abstract: Unlabelled Image Highlights: AM alloy shows higher peak stress and larger stress reduction than the HT one. Silicide evolution is restrained in hot deformed HT alloy compared with AM alloy. Nbss CDRX process is promoted in AM alloy compared to HT alloy at 1250 °C. AM alloy has slower CDRX process of Nbss and Nb5 Si3 than HT alloy at 1410 °C. Smaller Nbss grains form in AM alloy than in HT alloy in steady-state flow.